New European recommendations for MP staffing levels – application to Portugal. (September 2016) - Figueira, R.; Poli, E.; Isidoro, J.
Abstract : Introduction: The publication of the EC Guidelines on the Medical Physics Expert (RP174) and the updated EFOMP Policy Statement 7.1 provided european countries with a new reference for medical physics staffing levels according to the different areas of application. Purpose: To characterize the current portuguese situation and, using these newly published recommendations, identify the number of medical physicists required per area and compare with the existing situation. Materials and methods: Official data from Health Ministry documents, quantifying the number of radiological installations, equipments and clinical workload, were used as input for the calculation of the necessary staffing levels according to the recommendations. In parallel, data from a 2015 survey conducted by DFM-SPF were used to characterize the actual situation. A comparison between both was made for each area. Results: Based on the comparison between the recommended number of medical physicists and the current number, the real needs of the country were identified. The presence of medical physicists in Radiotherapy and Nuclear Medicine, although below the recommended number, is well established. That is not the case in Diagnostic and Interventional Radiology where there is a real lack of presence of medical physicists. Conclusion: This study allowed to identify areas of main concern in terms of medical physics staffing levels. The results highlight the existing deficit in the number of professionals and will be presented to national health authorities. It can be used as a tool for planning future education and training requirements to provide the country with the necessary qualified medical physicists to guarantee the quality and security of the radiological medical procedure Disclosure: The authors have nothing to disclose.